Urban Sexual Health Clinic Patients With "Undetermined Risk" for HIV Are Less Likely to Receive Preexposure Prophylaxis. Issue 11 (3rd November 2021) - Platt, Laura; Shebl, Fatma M.; Qian, Yiqi; Bunda, Bridget; Ard, Kevin L.; Bassett, Ingrid V.
Abstract : Sexual health clinic patients with no identified risk for HIV transmission are the second most numerous group with indications for preexposure prophylaxis but are the least likely to receive a prescription. Abstract : Background: New diagnoses of HIV increasingly occur among people who fall outside traditional transmission risk categories. This group remains poorly defined, and HIV prevention efforts for this group lag behind efforts for patients in other risk groups. Methods: We conducted a retrospective review of patient visits at sexual health clinics in Boston, MA, over a 14-month period. Patients were classified into Centers for Disease Control and Prevention–defined HIV transmission risk categories. We compared frequencies of sexually transmitted infections (STIs), HIV, preexposure prophylaxis (PrEP) indications, and PrEP prescriptions. Predictors of HIV or STI among patients in the undetermined risk category were assessed with logistic regression. Results: There were 4723 clinic visits during the study period. Patients in the undetermined risk group constituted the largest proportion (55.8%), followed by men who have sex with men (MSM; 42.7%). The proportion of visits by patients in the undetermined risk group with an indication for PrEP was low (28.0%) compared with MSM (91.3%) and MSM who also inject drugs (93.8%); however, the absolute number was high (737). Among patients with an indication for PrEP, those in the undetermined risk group were least likely to receive a prescription. Behavioral risk factors were poorly predictive of STI or HIV among patients in the undetermined risk group. Conclusions: Patients with undetermined risk for HIV constituted a large proportion of clinic visits and had a large volume of sexual health needs but rarely received PrEP when indicated. To end the HIV epidemic in the United States, prevention efforts must include people who fall outside traditional risk categories.